Potential laws on the changes of shale in acid erosion process based on the fast matching method of dimensional analysis. (11th February 2021) - Du, Shuheng
Abstract: The evolutionary laws of the physical and mechanical properties of shale reservoirs in the process of acid erosion have not been clarified. This paper provides the potential laws of pore size and the elastic modulus evolution of shale in the process of point-source acid erosion. The results show that the average pore size increment of the shale Δ r in the process of point-source acid erosion may be in accordance with the scaling law of two-fifth's power of the reaction time t, and the ratio of the elastic modulus E to the elastic modulus E 0 of the initial state which is E E 0 is in accordance with the scaling law of the negative third power of the ratio r r 0 . The conclusion of the study has both theoretical and practical significance for assisting the fossil energy exploitation and supply. Highlights: Fast matching method of dimensional analysis is powerful in geological discovery. Scaling laws need to be attached great importance in energy science. The theoretical model of acid erosion needs to be improved.